2023
DOI: 10.1038/s41539-023-00162-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter-brain coupling reflects disciplinary differences in real-world classroom learning

Abstract: The classroom is the primary site for learning. A vital feature of classroom learning is the division of educational content into various disciplines. While disciplinary differences could substantially influence the learning process toward success, little is known about the neural mechanism underlying successful disciplinary learning. In the present study, wearable EEG devices were used to record a group of high school students during their classes of a soft (Chinese) and a hard (Math) discipline throughout on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…This study conducted a comparative analysis of academic performance predictions based on student-teacher inter-brain coupling versus inter-brain coupling among students, thereby affirming the unique value of student-teacher coupling. Prior research has demonstrated the predictive effectiveness of student-class coupling in high school math and biology class, as well as the capacity of student-excellence coupling to forecast Chinese performance (Chen, Qian, et al, 2023;Dikker et al, 2017). This study found that student-class coupling for math learning offers superior predictive performance.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This study conducted a comparative analysis of academic performance predictions based on student-teacher inter-brain coupling versus inter-brain coupling among students, thereby affirming the unique value of student-teacher coupling. Prior research has demonstrated the predictive effectiveness of student-class coupling in high school math and biology class, as well as the capacity of student-excellence coupling to forecast Chinese performance (Chen, Qian, et al, 2023;Dikker et al, 2017). This study found that student-class coupling for math learning offers superior predictive performance.…”
Section: Discussionmentioning
confidence: 68%
“…A 'segment' was defined as a matched epoch, recognized as such only when it included artifact-free and valid data from both the teacher and the student. A minimum threshold was established, requiring that only student-teacher pairs with at least six valid segments were to be included (Chen, Qian, et al, 2023;Dikker et al, 2017). For Chinese classes, the average proportion of valid student-teacher coupling segments for each session was 50.2%, while for math classes, it was 46.6% (Fig.…”
Section: (𝑁−1)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting, however, that there may be different kinds of effective speech. For example, a speaker may seek to (mis)direct listeners toward a different understanding than their own; listeners that are unfamiliar versus experts with a particular topic may experience the same speech very differently (Meshulam et al, 2021; Chen et al, 2023); and a speaker may attempt to “meet certain listeners where they are” rather than wrangling all listeners similarly.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a given narrative has been shown to vary across individuals. Both higher LL neural coupling and higher SL neural coupling have been separately associated with better behavioral estimates of speech comprehension across individuals (Stephens et al, 2010; Zadbood et al, 2017; Cohen et al, 2018; Zheng et al, 2018; Davidesco et al, 2019, 2019; Liu et al, 2019, 2022; Pan et al, 2020; Meshulam et al, 2021; Nguyen et al, 2022; Zhang et al, 2022, 2022; Zhu et al, 2022; Chen et al, 2023). Individuals performing better in the post-test often showed higher neural coupling with the speaker or other listeners.…”
Section: Introductionmentioning
confidence: 99%